ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA DI SDN 066656 MEDAN - Sembiring, Polintan Rehulina; Tarigan, Paska Sriulina; Manik, Nova Betania (Universitas Quality, 2024)
Audio visual learning media makes it easier for students to understand material from the abstract to the more concrete so that students are able to understand the subject matter well, thereby improving student learning outcomes. This research aims to analyze the activities of using learning media in improving student learning outcomes. Data collection techniques through observation, documentation and interviews with class teachers. This research uses a qualitative descriptive approach. Based on research results, the use of audio-visual learning media has proven to be very effective in improving science learning outcomes, apart from that, there is also the involvement of internal and external factors in terms of student learning activities in class.